Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

Scaling up education reform: addressing the politics of disparity - Bishop, Russell (NZCER Press, 2010)
Keywords: education; educational change; mātauranga māori